Prognostic impact of expression of CD2, CD25, and/or CD30 in/on mast cells in systemic mastocytosis: a registry study of the European Competence Network on Mastocytosis - Rüfer, Axel; Nilius, Henning; Hermine, Olivier; Niedoszytko, Marek; Oude Elberink, Joanne N G; Bonadonna, Patrizia; Shoumariyeh, Khalid; Gulen, Theo; Hartmann, Karin; Sabato, Vito; Angelova-Fischer, Irena; Baffoe, Daniel; et al. (Leukemia, 2025)
Expression of CD2, CD25 and/or CD30 in extracutaneous mast cells (MC) is a minor diagnostic criterion for systemic mastocytosis (SM) in the classification of the World Health Organization and International Consensus Classification. So far, it remains unknown whether expression of these antigens on MC is of prognostic significance in SM. We performed a retrospective multi-center study of patients with SM using the data set of the registry of the European Competence Network on Mastocytosis, including 5034 patients with various MC disorders. The percentage of CD2-, CD25+ and/or CD30+ MC was considerably lower in patients with indolent SM compared to patients with advanced SM, including aggressive SM and MC leukemia. Whereas CD25 and CD30 expression in MC could not be associated with prognosis, we found that lack of CD2 expression in MC is associated with a significantly reduced overall survival (OS) in patients with SM (p < 0.0001). Lack of CD2 was also associated with the presence of extramedullary involvement affecting the spleen, liver, and/or lymph nodes (odds ratio 2.63 compared to SM with CD2+ MC). Together, lack of CD2 expression in MC is a prognostic marker and indicator of reduced OS and extramedullary disease expansion in patients with SM.
Keywords: senioři; systémová mastocytóza; mastocyty; senioři nad 80 let; Retrospective Studies; Europe; Prognosis; mladiství; CD2 Antigens; Evropa; Middle Aged; registrace; mužské pohlaví; Adult; mladý dospělý; receptor interleukinu-2 - alfa-podjednotka; Registries; dítě; Child; Aged, 80 and over; Young Adult; antigeny CD2; prognóza; ženské pohlaví; retrospektivní studie; Humans; antigen Ki-1; Ki-1 Antigen; lidé středního věku; Interleukin-2 Receptor alpha Subunit; Mast Cells; dospělí; Mastocytosis, Systemic; Female; Aged; Adolescent; lidé; Male